The Role of Health Literacy in Shaping Self-Management Skills and Healthy Lifestyle Behaviors among Migrant University Students Living in Boarding Houses - Youlia Opita Sibuea; Nabila Simamora; Mahfuzi Irwan; Khodijah Tussolihin (Parpudi: Journal Of Community and Adult Learning, 2025)
Migrant university students living in boarding houses face significant challenges in maintaining healthy lifestyles due to academic pressure, environmental changes, and limited access to health-supporting facilities. Health literacy plays a crucial role in enabling students to manage their health independently by accessing, understanding, evaluating, and applying health information. This study aims to analyze the role of health literacy in shaping self-management skills and healthy lifestyle behaviors among migrant students residing in boarding houses. A quantitative descriptive approach was employed using a structured online questionnaire distributed to 50 migrant students. The instrument measured dimensions of health literacy, physical health behaviors, mental health awareness, and self-management practices. Data were analyzed using descriptive statistics to identify behavioral trends and literacy patterns. The findings indicate that while students demonstrate relatively high access to digital health information, the application of health knowledge in daily practices such as balanced diet, regular physical activity, and adequate sleep remains inconsistent. Academic workload and economic constraints emerged as major barriers to healthy behavior. The study concludes that students’ health literacy is predominantly at a functional level and has not yet fully translated into sustainable self-management practices. These findings highlight the need for targeted health education interventions that promote critical and applied health literacy among migrant students.